Enhanced Immunogenicity of a Whole-Inactivated Influenza A Virus Vaccine Using Optimised Irradiation Conditions - Singleton, Eve Victoria; Gates, Chloe Jayne; David, Shannon Christa; Hirst, Timothy Raymond; Davies, Justin Bryan; Alsharifi, Mohammed (Frontiers in Immunology, 2021)
Influenza A virus presents a constant pandemic threat due to the mutagenic nature of the virus and the inadequacy of current vaccines to protect against emerging strains. We have developed a whole-inactivated influenza vaccine using gamma-irradiation (gamma-Flu) that can protect against both vaccine-included strains as well as emerging pandemic strains. Gamma-irradiation is a widely used inactivation method and several gamma-irradiated vaccines are currently in clinical or pre-clinical testing. To enhance vaccine efficacy, irradiation conditions should be carefully considered, particularly irradiation temperature. Specifically, while more damage to virus structure is expected when using higher irradiation temperatures, reduced radiation doses will be required to achieve sterility. In this study, we compared immunogenicity of gamma-Flu irradiated at room temperature, chilled on ice or frozen on dry ice using different doses of gamma-irradiation to meet internationally accepted sterility assurance levels. We found that, when irradiating at sterilising doses, the structural integrity and vaccine efficacy were well maintained in all preparations regardless of irradiation temperature. In fact, using a higher temperature and lower radiation dose appeared to induce higher neutralising antibody responses and more effective cytotoxic T cell responses. This outcome is expected to simplify irradiation protocols for manufacturing of highly effective irradiated vaccines.